2005
DOI: 10.1073/pnas.0505294102
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin D is a component of mitochondrial permeability transition and mediates neuronal cell death after focal cerebral ischemia

Abstract: Mitochondrial permeability transition (PT) is a phenomenon induced by high levels of matrix calcium and is characterized by the opening of the PT pore (PTP). Activation of the PTP results in loss of mitochondrial membrane potential, expansion of the matrix, and rupture of the mitochondrial outer membrane. Consequently, PT has been implicated in both apoptotic and necrotic cell death. Cyclophilin D (CypD) appears to be a critical component of the PTP. To investigate the role of CypD in cell death, we created a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
654
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 756 publications
(676 citation statements)
references
References 54 publications
17
654
4
1
Order By: Relevance
“…[18][19][20][21] Previous findings showed that CypD is an important regulator of MPT pores. 20,21 Importantly, because of the impaired MPT, CypD-deficient mice displayed a strong resistance against brain ischemic damage and motor neurons degeneration, 17,20 reminiscent of the ASIC1a-deficient mice. 5,6 Therefore, we tested the hypothesis that ASIC1a is a regulator (or even a structural component) of the MPT pore, presumably through association with CypD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[18][19][20][21] Previous findings showed that CypD is an important regulator of MPT pores. 20,21 Importantly, because of the impaired MPT, CypD-deficient mice displayed a strong resistance against brain ischemic damage and motor neurons degeneration, 17,20 reminiscent of the ASIC1a-deficient mice. 5,6 Therefore, we tested the hypothesis that ASIC1a is a regulator (or even a structural component) of the MPT pore, presumably through association with CypD.…”
Section: Resultsmentioning
confidence: 99%
“…13 Mitochondrial permeability transition (MPT) is a key event that occurs in most forms of cell demise (apoptotic, necrotic, autophagic or mitotic), determining the life and death of cells. [14][15][16] The opening of MPT pores causes an abrupt increase of inner mitochondrial membrane permeability to solutes with molecular masses of o1500 Da, 14,16,17 leading to mitochondrial swelling, disruption of the mitochondrial outer membranes and mitochondrial dysfunction. 14-16 Keywords: mitochondria; ASIC1a; MPT; oxidative cell death Abbreviations: Aldh7a1, aldehyde dehydrogenase 7 family member a1; AMI, amiloride; ANT, adenine nucleotide translocase; ASIC1a, acid-sensing ion channel 1a; [Ca 2 þ ] em , extramitochondrial Ca 2 þ concentrations; CRC, Ca 2 þ retention capacity; CsA, cyclosporin A; CTB, Cell-Titer Blue; CypD, cyclophilin D; Cyt C, cytochrome c; DNP, dinitrophenol; DC m , mitochondrial membrane potential; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; Gpd2, glycerol-3-phosphate dehydrogenase 2; Hibch, 3-hydroxyisobutyryl-CoA hydrolase; H 2 O 2 , hydrogen peroxide; MCU, mitochondrial Ca 2 þ uniporter; Mito-DsRed, mitochondrion-targeting red fluorescent protein; MPT, mitochondrial permeability transition; mtASIC1a, mitochondrial ASIC1a; MTCO2, cytochrome c oxidase subunit 2; Mterfd2, mitochondria transcription termination factor domain containing 2; PcTX1, psalmotoxin 1; PDI, protein disulfide isomerase; PI, propidium iodide; Pick1, protein interacting with protein kinase C 1; PIN1peptidylprolyl cis/trans isomerase NIMA-interacting 1; ROS, reactive oxygen species; Slc25a25, solute carrier family 25 member 25; TMRM, tetramethylrhodamine methylester; VDAC, voltage-dependent anion channel…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cypd seems to be crucial for MPTP−induced cell death as deficiency in Cypd protects neuron, cardiomyocytes and kidney in mice from ischaemia injury. Deficiency in Cypd protected MEF from necrosis induced by calcium overload or H 2 O 2 treatment 49. Cypd−mediated necrosis is also observed in the context of I/R linked pathologies as deficiency in Cypd will dramatically reduced the infarct size 49, 50.…”
Section: Mitochondrial Pathway Of Necrosismentioning
confidence: 98%